The loading direction dramatically affects the mechanical properties of the mouse tibia - Farage-O’Reilly, Saira Mary; Cheong, Vee San; Pickering, Edmund; Pivonka, Peter; Bellantuono, Ilaria; Kadirkamanathan, Visakan; Dall’Ara, Enrico (Frontiers in Bioengineering and Biotechnology, 2024)
The in vivo tibial loading mouse model has been extensively used to evaluate bone adaptation in the tibia after mechanical loading treatment. However, there is a prevailing assumption that the load is applied axially to the tibia. The aim of this in silico study was to evaluate how much the apparent mechanical properties of the mouse tibia are affected by the loading direction, by using a validated micro-FE model of mice which have been ovariectomized and exposed to external mechanical loading over a two-week period. Longitudinal micro-computed tomography (micro-CT) images were taken of the tibiae of eleven ovariectomized mice at ages 18 and 20 weeks. Six of the mice underwent a mechanical loading treatment at age 19 weeks. Micro-finite element (micro-FE) models were generated, based on the segmented micro-CT images. Three models using unitary loads were linearly combined to simulate a range of loading directions, generated as a function of the angle from the inferior-superior axis (θ, 0-30° range, 5° steps) and the angle from the anterior-posterior axis (ϕ, 0°: anterior axis, positive anticlockwise, 0-355° range, 5° steps). The minimum principal strain was calculated and used to estimate the failure load, by linearly scaling the strain until 10% of the nodes reached the critical strain level of -14,420 με. The apparent bone stiffness was calculated as the ratio between the axial applied force and the average displacement along the longitudinal direction, for the loaded nodes. The results demonstrated a high sensitivity of the mouse tibia to the loading direction across all groups and time points. Higher failure loads were found for several loading directions (θ=10°, ϕ=205-210°) than for the nominal axial case (θ=0°, ϕ=0°), highlighting adaptation of the bone for loading directions far from the nominal axial one. These results suggest that in studies which use mouse tibia, the loading direction can significantly impact the failure load. Thus, the magnitude and direction of the applied load should be well controlled during the experiments.